PATTERNS OF CORRUPTION CRIMINAL DEVELOPMENT IN SUKAMISKIN CLASS I CORRUPTION INSTITUTIONS - Kusmiyanti Kusmiyanti (Polteknik Ilmu Pemasyarakatan, 2018)
The purpose of this research is to observe the implementation of the guidance of corruption criminal prisoners in Sukamiskin Correctional institution. This research uses a qualitative approach. It concludes that the implementation of guidance in Sukamiskin Correctional Institution has not been in accordance with the concept of Correctional. The guidance on the prisoners of corruption is only the guidance of the personality. The strengthening of religious values conducted by ustadz, priests and other religious leaders. Development of independence does not fit with the concept of correctional. Therefore correctional officers must have expertise in the field and also must have a high sense of devotion. Correctional officers must uphold the concept of correctional based on the principles of Pancasila and continue to view prisoners as God's creatures, as individuals and as members of society.